Tracce di un’esperienza, memoria di uno spettacolo: Cosa resta di "Café Müller" di Pina Bausch nei ricordi degli spettatori - Franco, Susanne (Mimesis Journal, 2019)
The essay proposes a historical-theoretical reflection on Pina Bausch’s Café Müller (1978) and introduces and contextualizes the texts commissioned to Italian dance critics and scholars of different generations for the Café Müller Installation set up in November 2018 at La Lavanderia a Vapore (Collegno) as part of the Maratona Bausch project. Dancing memory, rethinking history. The event, curated by Susanne Franco, was conceived as a memory machine to pay homage to Pina Bausch ten years after her death, to the artistic heritage she left us and which has indelibly marked the theatre scene of the 20th and 21st centuries and, in particular, to forty years after her debut.